2019
DOI: 10.5194/acp-19-11343-2019
|View full text |Cite
|
Sign up to set email alerts
|

The ice-nucleating ability of quartz immersed in water and its atmospheric importance compared to K-feldspar

Abstract: Abstract. Mineral dust particles are thought to be an important type of ice-nucleating particle (INP) in the mixed-phase cloud regime around the globe. While K-rich feldspar (K-feldspar) has been identified as being a particularly important component of mineral dust for ice nucleation, it has been shown that quartz is also relatively ice-nucleation active. Given quartz typically makes up a substantial proportion of atmospheric desert dust, it could potentially be important for cloud glaciation. Here, we survey… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
176
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(189 citation statements)
references
References 76 publications
(165 reference statements)
13
176
0
Order By: Relevance
“…However, although the Saharan dust was transported over several thousands of kilometers across the Atlantic Ocean, observations suggest that the dust in the SAL remained nearly unprocessed (Lieke et al, 2011;Denjean et al, 2015;Weinzierl et al, 2017;Kandler et al, 2018). Therefore, κ should not change significantly during transport and be closer to the value for fresh Saharan dust which is taken from laboratory studies (Koehler et al, 2009;Herich et al, 2009;Kumar et al, 2011a, b). Twohy et al (2009) found good agreement for their CCN measurements with a κ of 0.05 in the eastern Atlantic.…”
Section: Lidar Retrievals Of Ccn and Inp Concentrationsmentioning
confidence: 92%
See 2 more Smart Citations
“…However, although the Saharan dust was transported over several thousands of kilometers across the Atlantic Ocean, observations suggest that the dust in the SAL remained nearly unprocessed (Lieke et al, 2011;Denjean et al, 2015;Weinzierl et al, 2017;Kandler et al, 2018). Therefore, κ should not change significantly during transport and be closer to the value for fresh Saharan dust which is taken from laboratory studies (Koehler et al, 2009;Herich et al, 2009;Kumar et al, 2011a, b). Twohy et al (2009) found good agreement for their CCN measurements with a κ of 0.05 in the eastern Atlantic.…”
Section: Lidar Retrievals Of Ccn and Inp Concentrationsmentioning
confidence: 92%
“…Cloud-processed Saharan dust particles (mimicked by wetgenerated dust samples) may have changed their hygroscopic properties (higher κ value) so that their CCN efficacy increased. Laboratory studies with wet-generated dust particles (in contrast to dry-generated fresh dust particles) reported higher κ values (Koehler et al, 2009;Herich et al, 2009;Kumar et al, 2011b). However, although the Saharan dust was transported over several thousands of kilometers across the Atlantic Ocean, observations suggest that the dust in the SAL remained nearly unprocessed (Lieke et al, 2011;Denjean et al, 2015;Weinzierl et al, 2017;Kandler et al, 2018).…”
Section: Lidar Retrievals Of Ccn and Inp Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent field activities with a focus on ice-nucleating particle concentration (INPC) were reported by Schrod et al (2017), Welti et al (2018), McCluskey et al (2017McCluskey et al ( , 2018a, Price et al (2018), and Wex et al (2019). More than 30 years of airborne observations in mixed-phase and cirrus clouds have improved our understanding of ice formation processes and have provided a wealth of information on the microphysical properties of ice clouds (see the review articles of Heymsfield et al, 2017. Prenni et al (2009) were, to our knowledge, the first who successfully performed closure studies on the relationship between the INPC and ice crystal number concentration (ICNC), based on airborne in situ observations.…”
mentioning
confidence: 99%
“…Overall, heat-sensitive components dominated the freezing at higher temperatures (above -15 ℃), and their contribution decreased pronouncedly at lower temperatures. Recently, Harrison et al (2019) found that some quartz samples are sensitive to aging in aqueous suspension. We can't rule out the presence of quartz, or determine the fraction of specific quartz in heatsensitive INPs at -20 ℃.…”
Section: Contribution Of Heat-sensitive Inpsmentioning
confidence: 99%